We need an international support programme for sustainable investment facilitation - Karl P. Sauvant (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2015)
The WTO's Trade Facilitation Agreement needs to be complemented by an international support program for sustainable investment facilitation. Key elements are outlined and approaches suggested.
Keywords: 330